The Principle of Education According to The Perspective of Hasan bin Ali Al-Hajjajy And John Dewey - Akbar Aisya Billah; Ulum, M. Miftahul (EDUCAN : JURNAL PENDIDIKAN ISLAM, 2024)
Education is a basic need and right of every human being. With this education, humans get a decent and good life. The educational building stands strong and firm on a solid foundation of thought. This is where educational thinkers' urgency is in supporting these buildings' establishment. Not only related to the building's strength, style, and model is also very dependent on the style of thought of the characters. This research is a literature study or library research. Data were taken from related literature in books, journals, and various sources. The data is then processed and analyzed critically and in-depth using content analysis. The study results show that there are different perspectives on the principles of education according to Islam, represented by Hasan bin Ali Al-Hajjajy, and a Western perspective, represented by John Dewey. Each perspective gave birth to different styles and education models, so the products produced also differ.